2018
DOI: 10.3389/fmicb.2018.02949
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3β Enhances Hepatitis C Virus Replication by Supporting miR-122

Abstract: Hepatitis C virus (HCV) infection is associated with alterations in host lipid and insulin signaling cascades, which are partially explained by a dependence of the HCV life cycle on key molecules in these metabolic pathways. Yet, little is known on the role in the HCV life cycle of glycogen synthase kinase 3 (GSK3), one of the most important kinases in cellular metabolism. Therefore, the impact of GSK3 on the HCV life cycle was assessed in human hepatoma cell lines harboring subgenomic genotype 1b and 2a repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…In hepatitis C virus (HCV)-treated human hepatocarcinoma Huh7.5 cells, GSK3 inhibitors prevented the release of HCV virions, while viral replication was not affected [174]. Another group found that GSK3β (but not GSK3α) inhibition reduced both replication and viral particle production of HCV but not hepatitis E virus in Huh7.5 cells [175]. Moreover, GSK3-mediated phosphorylation appears to be involved in the destabilization of PHD finger protein 13, a host factor that (amongst other functions) is involved in repressing HIV-1 [176] and human cytomegalovirus gene expression [177].…”
Section: Role Of Gsk3 During Viral Infectionsmentioning
confidence: 99%
“…In hepatitis C virus (HCV)-treated human hepatocarcinoma Huh7.5 cells, GSK3 inhibitors prevented the release of HCV virions, while viral replication was not affected [174]. Another group found that GSK3β (but not GSK3α) inhibition reduced both replication and viral particle production of HCV but not hepatitis E virus in Huh7.5 cells [175]. Moreover, GSK3-mediated phosphorylation appears to be involved in the destabilization of PHD finger protein 13, a host factor that (amongst other functions) is involved in repressing HIV-1 [176] and human cytomegalovirus gene expression [177].…”
Section: Role Of Gsk3 During Viral Infectionsmentioning
confidence: 99%
“…GSK3b is known as an AKT substrate which plays a crucial role in influenza viral entry (13,14). GSK3b silence could decrease the hepatitis C virus (HCV) replication and the production of infectious particle while GSK3b overexpression enhanced HCV replication (15). Studies in vitro displayed that specific inhibitors (small molecules) of GSK3b significantly decreased Tat-dependent replication of human immunodeficiency virus 1 (HIV1) (16).…”
Section: Introductionmentioning
confidence: 99%
“… 254 , 255 The overexpression of GSK-3β has been associated with HCV entry. 256 In HIV-1 infected T cells and monocytic cell lines, the upregulation of GSK-3β has been identified. 257 Coxsackievirus B3 (CVB3) infection induced GSK-3 expression in HeLa cell lines and a mouse model, resulting in virus-driven cytopathic effects and apoptosis.…”
Section: Kinase Pathway Inhibitors As Anti-inflammatory Cytokine-suppressive or Antifibrotic Agents In Covid-19mentioning
confidence: 99%
“… 260 , 257 In Huh 7.5 cells, inhibition of GSK-3β led to a reduction of both replication and viral particle production of HCV but for hepatitis E virus (HEV). 261 The increased GSK-3β-Ser9 phosphorylation has been linked to the replication of the HBV, 262 , 263 indicating a beneficial effect of GSK-3β inhibition for HBV replication. GSK-3 phosphorylation of assembly protein precursor, a protein involved in the organization and maturation of cytomegalovirus, is required.…”
Section: Kinase Pathway Inhibitors As Anti-inflammatory Cytokine-suppressive or Antifibrotic Agents In Covid-19mentioning
confidence: 99%